Fenomena ibu postpartum dengan bayi lahir prematur - Sona, Sri; Aramico, Basri; Nahrisah, Putri; Ichwamsyah, Fahmi; Zakaria, Radhiah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Premature birth is a challenging experience for postpartum mothers, not only medically but also emotionally and psychologically. Premature babies often require care in the neonatal intensive care unit (NICU), which can increase maternal anxiety, guilt, and stress. This condition can potentially lead to postpartum depression, severe anxiety, and even psychological trauma that impact the quality of care for the baby. Purpose: To explore the phenomenon of postpartum mothers with premature babies. Method: This qualitative study used phenomenological methods, covering emotional experiences, coping strategies, family support, and healthcare workers' perspectives on postpartum mothers with premature babies. Participants included six postpartum mothers, three family members, and two healthcare workers at the Aceh Government Women and Children's Hospital. Data were obtained through in-depth interviews and analyzed thematically to identify themes and subthemes within the participants' experiences. Results: Five main themes emerged: the phenomenon of preterm birth and postpartum maternal conditions, maternal emotional and psychological well-being, emotional support and the role of the family, coping strategies and spirituality, and healthcare workers' perspectives on psychosocial support. Findings show that mothers experience drastic emotional changes, ranging from sadness and stress to despair. Partner and family support plays a crucial role as psychological support, while spirituality is a dominant coping mechanism. However, healthcare professionals still focus more on the baby's condition and have not optimally provided psychosocial support to mothers. Conclusion: Premature birth creates a profound emotional crisis for postpartum mothers. Family support, empathetic communication from healthcare professionals, and structured psychosocial interventions are essential to help mothers navigate these challenges. Keywords: Coping Strategies; Mental Health; Postpartum Mother; Premature Infant; Social Support. Pendahuluan: Kelahiran bayi prematur merupakan pengalaman yang penuh tantangan bagi ibu postpartum, tidak hanya dari aspek medis tetapi juga emosional dan psikologis. Bayi prematur sering membutuhkan perawatan di NICU, yang dapat meningkatkan rasa cemas, bersalah, dan stres pada ibu. Kondisi ini berpotensi menimbulkan depresi postpartum, kecemasan berat, bahkan trauma psikologis yang memengaruhi kualitas pengasuhan bayi. Tujuan: Untuk mengeksplorasi fenomena ibu postpartum dengan bayi lahir prematur. Metode: Penelitian kualitatif dengan metode fenomenologi yang mencakup pengalaman emosional, strategi koping, dukungan keluarga, serta pandangan tenaga kesehatan terhadap ibu postpartum dengan bayi lahir prematur. Partisipan terdiri dari 6 ibu postpartum, 3 anggota keluarga, dan 2 tenaga kesehatan di Rumah Sakit Ibu dan Anak Pemerintah Aceh. Data diperoleh melalui wawancara mendalam dan dianalisis secara tematik untuk mengidentifikasi tema dan subtema pengalaman partisipan. Hasil: Lima tema utama yang didapat yaitu fenomena kelahiran prematur dan kondisi ibu postpartum, kesejahteraan emosional dan psikologis ibu, dukungan emosional dan peran keluarga, strategi koping dan spiritualitas, serta pandangan tenaga kesehatan terhadap dukungan psikososial. Temuan memperlihatkan bahwa ibu mengalami perubahan emosi drastis, mulai dari kesedihan, stress hingga keputusasaan. Dukungan pasangan dan keluarga berperan penting sebagai penyangga psikologis, sementara spiritualitas menjadi mekanisme koping yang dominan. Namun, tenaga kesehatan masih lebih fokus pada kondisi bayi dan belum optimal dalam memberikan pendampingan psikososial bagi ibu. Simpulan: Kelahiran prematur menimbulkan krisis emosional mendalam bagi ibu postpartum. Dukungan keluarga, komunikasi empatik tenaga kesehatan, serta intervensi psikososial yang terstruktur sangat dibutuhkan untuk membantu ibu menghadapi tantangan tersebut. Kata Kunci: Bayi Prematur; Dukungan Sosial; Ibu Postpartum; Kesehatan Mental; Strategi Koping.